2009
DOI: 10.1175/2008jcli2679.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Anthropogenic Changes in the Brewer–Dobson Circulation, Including Its Extension to High Latitudes

Abstract: Recent studies using comprehensive middle atmosphere models predict a strengthening of the Brewer–Dobson circulation in response to climate change. To gain confidence in the realism of this result it is important to quantify and understand the contributions from the different components of stratospheric wave drag that cause this increase. Such an analysis is performed here using three 150-yr transient simulations from the Canadian Middle Atmosphere Model (CMAM), a Chemistry–Climate Model that simulates climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

57
257
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(317 citation statements)
references
References 30 publications
57
257
3
Order By: Relevance
“…Lack of a robust temperature response, however, is perhaps not surprising given that (1) any temperature trend in the wintertime ALS will likely be small in amplitude, due the close balance between enhanced diabatic CO 2 cooling and the predicted adiabatic warming accompanying a strengthened mean-meridional circulation McLandress and Shepherd, 2009b) and (2) trends may also be contaminated by the large component of interannual variability common to the region, in particular that due to the occurrence of stratospheric sudden warming (SSW) events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of a robust temperature response, however, is perhaps not surprising given that (1) any temperature trend in the wintertime ALS will likely be small in amplitude, due the close balance between enhanced diabatic CO 2 cooling and the predicted adiabatic warming accompanying a strengthened mean-meridional circulation McLandress and Shepherd, 2009b) and (2) trends may also be contaminated by the large component of interannual variability common to the region, in particular that due to the occurrence of stratospheric sudden warming (SSW) events.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted changes in stratospheric wave drag that influence the mean-meridional circulation Garcia and randel, 2008;McLandress and Shepherd, 2009b) are also likely to have an impact on the variability of the NH polar vortex, although relatively few studies to date have explicitly investigated such a possibility. In a 2×CO 2 simulation, Rind et al (1998) reported a decrease in the frequency of SSW events compared to their control simulation.…”
Section: Introductionmentioning
confidence: 99%
“…This fact 5 ensures the validity of the steady state assumption for solstitial seasons, which are frequently made for the diagnostics using the downward control principle (e.g., McLandress and Shepherd, 2009). It is interesting that the magnitude of Ψ / , in the summer low-latitude region is comparable to that of Ψ , but confined in the lower stratosphere.…”
Section: Stream Functions In Solstitial Seasonsmentioning
confidence: 71%
“…This principle indicates that the Coriolis torque for the residual mean meridional flow is balanced with the wave forcing in a steady state. The contribution of each wave to the residual mean flow can be evaluated using this 10 principle (McLandress and Shepherd, 2009). Okamoto et al (2011) applied this method to the ERA-Interim data (Dee et al, 2011) and to the outputs of a chemistry climate model (CCM) and showed that the GW forcing contributes to the formation of the summer hemispheric part of the deep branch of the winter circulation where RWs hardly propagate in the mean easterly wind of the summer stratosphere (Charney and Drazin, 1961), and to the formation of the shallow branches where orographic GWs break in the weak wind layer in the lower stratosphere (Lilly and Kennedy, 1973;Sato, 1990;Tanaka, 1986).…”
mentioning
confidence: 99%
See 1 more Smart Citation